PROFIT EFFICIENCY IN PRODUCTION OF SOME SELECTED UNDERUTILISED INDIGENOUS VEGETABLES IN SOUTH WEST NIGERIA FROM GENDER PERSPECTIVE - TANIMONURE, V. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
The study determined the profit efficiency and its determinants of producers of Telfairia occidentalis, Solanum macrocarpon, Amaranthus viridis and Solanecio biafrae. A multi-stage sampling technique involving the purposive selection of four States in Southwest Nigeria, where NICANVEG project was implemented was used. Proportionate and simple random sampling techniques were employed to select 194 producers. Primary data were collected using a structured questionnaire. Stochastic Frontier Profit Function (SFPF) was used to determine the profit efficiency and its determinants. The study found that UIVs producers were profit efficient. Male producers were significantly (t=2.65, p<0.05 and 2.45, p<0.05) more efficient in the production of T. occidentalis and S. biafrae but the female producers were significantly (t=-2.56, p=0.05 and t=-2.16, p=0.05) more efficient in the production of S. macrocarpon and A. viridis.  The factors that determined the profit efficiency of the UIVs producers include quantity of UIVs produced, value added, cost of production and the worth of quantity wasted. The socioeconomic factors that determined the inefficiency of the UIVs producers were age, farming experience, gender, education, farm distance from home and household size. In conclusion, a high profit efficiency levels found for the UIVs producers in the study is an ample sign that UIVs have the potential to generate higher household income, especially for women folks.